2005
DOI: 10.4049/jimmunol.174.9.5805
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Recruitment of Lymphocytes in Inflamed Brain Venules Requires Expression of Cutaneous Lymphocyte Antigen and Fucosyltransferase-VII

Abstract: Lymphocyte migration into the brain represents a critical event in the pathogenesis of multiple sclerosis and its animal model, experimental autoimmune encephalomyelitis (EAE). However, the mechanisms controlling the recruitment of lymphocytes to the CNS via inflamed brain venules are poorly understood, and therapeutic approaches to inhibit this process are consequently few. In this study, we demonstrate for the first time that human and murine Th1 lymphocytes preferentially adhere to murine inflamed brain ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 55 publications
4
35
0
1
Order By: Relevance
“…It has recently been reported that Fuc-T VII participates in the synthesis of CLA in the murine system. 49 Our results suggest that this enzyme is involved in the synthesis of sialyl 6-sulfo Le x in human skin-homing cells. Helper memory T cells and NK cells exhibit constitutive activation of HEC-GlcNAc6ST and Fuc-T VII compared with other human peripheral lymphocyte subpopulations.…”
Section: Discussionmentioning
confidence: 74%
“…It has recently been reported that Fuc-T VII participates in the synthesis of CLA in the murine system. 49 Our results suggest that this enzyme is involved in the synthesis of sialyl 6-sulfo Le x in human skin-homing cells. Helper memory T cells and NK cells exhibit constitutive activation of HEC-GlcNAc6ST and Fuc-T VII compared with other human peripheral lymphocyte subpopulations.…”
Section: Discussionmentioning
confidence: 74%
“…These results suggest that NaB prevents adhesion and transendothelial migration of encephalitogenic lymphocytes by suppressing the expression of integrins and adhesion molecules. Similarly, the role of E-and P-selectins in the extravasation of T lymphocytes into the CNS is also evident when complete inhibition of rolling and arrest of Th1 cells in inflamed brain was observed with anti-E-and P-selectin Abs (23). Interestingly, NaB was also found to inhibit the expression of E-and P-selectins in the cerebellum as well as in the spinal cord of EAE mice.…”
Section: Discussionmentioning
confidence: 84%
“…These approaches have even demonstrated that different molecular mechanisms guide CD8 + T cells and CD4 + T cells into the CNS, as CD8 + T cells from MS patients were shown to preferentially roll via P-selectin glycoprotein ligand (PSGL-1), whereas CD4 + T cells rolled via α4-integrin [11]. In addition, these studies showed that specifically the carbohydrate modification of PSGL-1 known as the cutaneous lymphocyte antigen (CLA) is required for leukocyte rolling in superficial brain vessels [12]. During EAE, both, α4-integrin and PSGL-1 were shown to mediate the rolling of endogenous leukocytes in inflamed superficial brain vessels [8].…”
Section: The Role Of Selectins and Psgl-1 In Leukocyte Trafficking Acmentioning
confidence: 97%